Cultivating Moral Values and Diversity for Early Childhood: A Contextual Approach of Multicultural Education - Kusumawati , Maulida; Hasanah, Nor Izzatil (Muadalah, 2024)
Cultivating the foundations of moral values and diversity in children is important from an early developmental stage. This article aims to explain how teachers introduce aspects of multicultural education to children. This research uses a qualitative research design in the form of a case study with seven teachers as respondents. Data were collected through observation, interview, and documentation techniques and then analyzed using thematic analysis consisting of three steps recommended by Miles and Huberman, namely data reduction, data presentation, and inference. The results showed that in introducing diversity, teachers provide role models for children, integrate material about cultural diversity into the learning curriculum, use interesting learning methods and media, invite children to visit historical sites and places of worship, hold activities and celebrate holidays related to cultural diversity, and hold extracurricular activities to introduce cultural diversity. It is expected that this article will have significant implications for educational practice, for ongoing professional development to equip teachers with the skills and knowledge needed to effectively teach and model diversity and inclusion, and for educational institutions to prioritize the development and implementation of curricula that reflect and celebrate cultural diversity.